The impact of macroeconomic variable movements on stock price index performance in consumer goods industry sector companies: Evidence from Indonesia - Zuhri, Elegi; Suskim Riantani (Technium Social Sciences Journal, 2020)
This research essentially aims to examine the extent to which macroeconomic variables (including inflation, exchange rate, and interest rate) have a significant influence on stock price index and the level of significance for that influence. The researchers focused more on consumer goods industry companies that are listed on the Indonesian Stock Exchange (IDX) within 2015 until 2019, with consideration for the stock price of consumer goods companies listed on the Indonesia Stock Exchange (IDX) as claimed to be the most defensive stock. This study finds that inflation, exchange rate, and interest rate, as composite variables, have a significant influence on stock price index. A partial test revealed that inflation, and exchange rate have negative significant influence on stock price index, while interest rate is found to be nonsignificant.